Gold Nanoparticles Array Growth from an Aqueous Solution on the Conductive Surface - V. Kusnezh; H. Ilchuk; F. Tsupko; M. Świniarski; Е.О. Zmiiovska (Журнал нано- та електронної фізики)
The chemical growth from an aqueous solution of simple, inexpensive components: formaldehyde, Na2CO3 and AuCl3 of the gold nanoparticles (AuNPs) array on the ITO films was considered. The gold nanoparticles growth kinetics in the aqueous environment was studied investigated on the basis of the optical absorption and plasmon maximum absorption position change in the growth process. The growth conditions were selected for growth on a solid surface and AuNPs arrays on the ITO films were fabricated. Surface morphology in the reflected and secondary electrons mode was investigated and AuNPs average size was determined. The wavelengths of plasmon resonance were defined from the measured absorption spectra of the samples in visible region.